Corrections (Pemasyarakatan) after Law Number 22 of 2022: New Principles and Policy Identification Regarding the Functions of Probation and Parole Offices - Iqrak Sulhin (Law and Human Rights Research and Development Agency, 2022)
The enactment of Law Number 22 of 2022 concerning Corrections (Pemasyarakatan), which replaces the previous Law Number 12 of 1995, significantly changes the implementation of Correctional functions, mainly the functions carried out by Probation and Parole Offices. If in the 1995 Law Corrections is only referred to as the final part of the Criminal Justice System, the new Law emphasizes the position of Corrections which are more integrated with the entire criminal justice process, so that Correctional functions are carried out at the pre-adjudication, adjudication, and post-adjudication stages. This amendment to the law is also interesting to be studied conceptually, especially to find out what principles are contained in it that form the basis for implementing the functions of Corrections. In line with this, it is also essential to identify what kind of policy changes should be carried out regarding the functions of Probation and Parole Offices in the future with the existence of new principles and differences of provisions in terms of the implementation of corrections functions. By using conceptual analysis methods, particularly policy detection analysis, which is technically carried out in two stages; first, the analysis stage of the content of the law and second, the theoretical coherence analysis stage, this paper comes to two conclusions. First, this paper finds an affirmation of new principles in Law Number 22 of 2022, namely the principle of restorative reintegration, the principle of evidence-based treatments, the principle of individualization, the principle of continuity, and the principle of collaboration. Second, this paper identifies 5 (five) policy changes that need to be made regarding the function of the Probation and Parole Office according to those principles. The policies that must be implemented can be divided into three groups—first, the need for further operationalization of the restorative reintegration concept described by this law. Second, the need for reformulation of various instruments needed in implementing functions, especially social inquiry reports. Third, the need for facilitative strengthening, especially the quantity and quality of probation and parole officers and other facilitative supports.